2016
DOI: 10.1002/smll.201600973
|View full text |Cite
|
Sign up to set email alerts
|

Ordered and Active Nanochannel Electrode Design for High‐Performance Electrochemical Actuator

Abstract: A novel electrochemical actuator based on polyaniline@vertically aligned carbon nanotube nanocomposite electrodes, in which the vertically aligned structure is introduced by a facilely electrochemical process. Owing to the vertically aligned nanocomposite electrode providing ordered path channel for faster ion transportation and high electrochemical capacitance for more ion accumulation, our actuator displays intriguing actuation performance including large deformation, fast-actuation speed, and excellent actu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 52 publications
(67 reference statements)
1
47
0
Order By: Relevance
“…Meanwhile, the aniline monomers in electrolyte lost electron and were in-situ electrodeposited on the carbon nanotubes. Besides, the positive charged particle would be moved3435 to the electric field’s direction so that CNTs was accelerate to be vertical alignment36, leading to the increase of CNTs film. Then, PANI would continue to grow until they filled the entire network.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the aniline monomers in electrolyte lost electron and were in-situ electrodeposited on the carbon nanotubes. Besides, the positive charged particle would be moved3435 to the electric field’s direction so that CNTs was accelerate to be vertical alignment36, leading to the increase of CNTs film. Then, PANI would continue to grow until they filled the entire network.…”
Section: Resultsmentioning
confidence: 99%
“…3b. However the capacitance would be decreased with electrochemical-induced time exceeding 60 min because the overgrowth PANI could not only inefficiently interact with VA-CNTs but also hinder the ion diffussion2936. The detailed specific capacitance variation was estimated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4b). The literature values were collected from independent references published during the past 13 years691325293031323334353637. This confirmed that the actuators based on nanostructured single-ion conductors enable the successful actuator operation with a micropower consumption, thus paving the way for more advanced biomimetic technologies in the future.…”
Section: Resultsmentioning
confidence: 53%
“…Over the past decade, a great number of materials including electromagnetic, electrostatic, piezoelectric, electrostrictive, magnetostrictive, shape memory alloy, responsive polymer, and hydrogel actuation material have been developed for smart devices applications. Electroincited materials can convert electrical energy into mechanical motions, which has found wide applications in the field of micro robots, sensors, artificial muscles, and bionic devices .…”
Section: Introductionmentioning
confidence: 99%